DNA Length Dependence of the Single-Strand Annealing Pathway and the Role of Saccharomyces cerevisiae RAD59 in Double-Strand Break Repair - Sugawara, Neal (American Society for Microbiology, 2000)
A DNA double-strand break (DSB) created by the HO endonuclease in Saccharomyces cerevisiae will stimulate recombination between flanking repeats by the single-strand annealing (SSA) pathway, producing a deletion. Previously the efficiency of SSA, using homologous sequences of different lengths, was measured in competition with that of a larger repeat further from the DSB, which ensured that nearly all cells would survive the DSB if the smaller region was not used (N. Sugawara and J. E. Haber, Mol. Cell. Biol. 12:563–575, 1992). Without competition, the efficiency with which homologous segments of 63 to 205 bp engaged in SSA was significantly increased. A sequence as small as 29 bp was used 0.2% of the time, and homology dependence was approximately linear up to 415 bp, at which size almost all cells survived. A mutant with a deletion of RAD59, a homologue of RAD52, was defective for SSA, especially when the homologous-sequence length was short; however, even with 1.17-kb substrates, SSA was reduced fourfold. DSB-induced gene conversion also showed a partial dependence on Rad59p, again being greatest when the homologous-sequence length was short. We found that Rad59p plays a role in removing nonhomologous sequences from the ends of single-stranded DNA when it invades a homologous DNA template, in a manner similar to that previously seen with srs2 mutants. Δrad59 affected DSB-induced gene conversion differently from msh3 and msh2, which are also defective in removing nonhomologous ends in both DSB-induced gene conversion and SSA. A msh3 rad59 double mutant was more severely defective in SSA than either single mutant.